NEEDS ANALYSIS OF PALEMBANG-TOURIST-DESTINATION RECOUNT TEXT READING MATERIALS IN THE 21ST CENTURY LEARNING - Yeni Oktarina; Rita Inderawati; Ismail Petrus (University of Kuningan, 2022)
The specification of the materials taught is one of the characteristics of teaching English at vocational high school. The materials should be appropriately designed or developed for the students to enhance their comprehension and to facilitate subject matter. The aim of this research is to look into students' needs for developing English reading materials based on Palembang culture, as determined by the feedback of students and teacher. Through a questionnaire and interview, the data were obtained. The data was quantitatively and qualitatively analysed. The results of the study revealed that 1) students are still experiencing some difficulty in reading comprehension, 2) a recount text is necessary; 3) English reading materials need to be integrated with students' local culture; and 4) no English reading material has been made available to incorporate the students' local culture, particularly in the field of tourism destination of Palembang. Due to needs, reading materials must be developed through the integration of local culture that matches the level of reading and supports the content of the topics.